Sistem Digitalisasi Data Kependudukan Di Desa Medan Krio Kecamatan Sunggal - Devita Ginting; Tuti Awaliyah (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
One of the backgrounds for the implementation of bureaucratic reforms in the population data digitization system is the quality of public services that have not met community expectations, in the sense that the level of public satisfaction is still low, marked by the number of complaints against public service providers, both related to service procedures that community expectations, in the sense that the level of public satisfaction is still low, marked by the number of complaints against public service providers, both those related to service procedures that still seem convoluted delays in management, unaffordable costs and the attitude of service officers that do not reflect the attitude of being a servant of the community. This research designed a digitalization system for population data collection at the Medan Krio village office which will later help village officials and the community in managing new family cards and birth certificates without queuing using a web-based system.